2021
DOI: 10.1016/j.ijom.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fit analysis of the patient-specific Groningen temporomandibular joint prosthesis

Abstract: Total joint replacement (TJR) with a prosthesis can be indicated for patients with severe temporomandibular joint (TMJ) dysfunction. Surgical accuracy is necessary for correct translation of the preoperatively predicted functional outcome, wear, and biomechanical behaviour of the patient-specific TMJ-TJR prosthesis. This study describes the first clinical applications of the patient-specific TMJ-TJR prosthesis according to the Groningen principles (G-TMJ-TJR), which was developed and validated in a prior human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This was done by allowing the replaced side to move synchronously with the other joint during both rotational movements with the other joint and vice versa, as well as during translative movements (e.g., when performing movements of opening and closing, both the healthy and replaced condyle should move without causing interferences in each other’s joint space). In comparison with the Groningen TMJ prosthesis, where a more bulky fossa component with a low rotational point is used, 16 the articular surface of the TMJ is placed more cranial, to allow for a more natural movement. The same study, concerning the Groningen TMJ prosthesis, did indicate that a more accurate planning and prediction was feasible thanks to the patient-specific fit.…”
Section: Methodsmentioning
confidence: 99%
“…This was done by allowing the replaced side to move synchronously with the other joint during both rotational movements with the other joint and vice versa, as well as during translative movements (e.g., when performing movements of opening and closing, both the healthy and replaced condyle should move without causing interferences in each other’s joint space). In comparison with the Groningen TMJ prosthesis, where a more bulky fossa component with a low rotational point is used, 16 the articular surface of the TMJ is placed more cranial, to allow for a more natural movement. The same study, concerning the Groningen TMJ prosthesis, did indicate that a more accurate planning and prediction was feasible thanks to the patient-specific fit.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this effect, the Groningen TMJ-TJR prosthesis was developed [7][8][9]. Apart from its unique feature that allows for free translational movement of the neo-disc, the prosthesis applies a lowered centre of rotation (CR) in relation to the anatomical condylar centre [8].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this effect, the Groningen TMJ-TJR prosthesis was developed [7][8][9]. Apart from its unique feature that allows for free translational movement of the neo-disc, the prosthesis applies a lowered centre of rotation (CR) in relation to the anatomical condylar centre [8]. Prior research suggested that a lowering of 15 [mm] in relation to the condyle would be optimal as a fixed CR for unilateral TMJ prostheses [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations